A New Combination in Holodiscus (Rosaceae, Amygdaloideae, Spiraeeae) - Potter, Daniel; Raiche, Roger (Phytotaxa, 2020)
Holodiscus dumosus var. cedrorum, The Cedars oceanspray, was described in 2011 in recognition of the distinct morphology of populations occurring on serpentine soils in The Cedars area in the Outer Coast Ranges of Sonoma County, California. Morphological and genetic data suggest that this taxon should instead be treated as a variety of Holodiscus discolor, here interpreted broadly as a widespread and highly variable species with several taxonomic varieties that intergrade. The new combination Holodiscus discolor var. cedrorum is made and a key to the varieties that occur in California is provided.